Stand-alone anterior cervical decompression and fusion surgery: A cohort study evaluating a shaped cage without plates or screws - Chen, Xiaolong; Sial, Alisha; Stewart, Charmian; Vargas Castillo, Jose; Diwan, Ashish D. (Frontiers in Surgery, 2022)
Background: The anterior approach to the cervical spine is the commonly used surgery with effective decompression and less surgical trauma. Anterior plate construct (APC) is considered as standard technique. However, it appears to cause implant failure and post-operative dysphagia. Due to these reasons, locking stand-alone cages (LSC) without the addition of an anterior plate has been developed and gained popularity in the past decade. In theory, a LSC could provide immediate load bearing support to anterior column of cervical spine and may enhance the rate of arthrodesis. However, screw skiving and backing off are known complications of LSC. Given the characteristic shape of cervical discs, we wondered whether there may be a role for a shape conforming cage without screws and plates to achieve desired outcomes i.e., a true stand-alone cage (TSC). A single surgeon cohort using the cage in a heterogenic set of indications was evaluated. Methods: Forty-five patients with degenerative cervical conditions who underwent TSC using CoRoent Small Contoured peek cage (Nuvasive San Diego CA) and Orthoblend™ (Medtronics Memphis TN) were retrospectively reviewed. Comparisons between pre- and post-operative Numerical Rating Scale (NRS), the modified AAOS-Modems disability outcome, Neck Disability Index (NDI) scores, and Short Form 36 (SF-36) were evaluated. Operative time, the occurrence rate of fusion, lordosis change of cervical spine, and occurrence rate of complications were evaluated. Results: There were 1-level (n=15), 2-levels (n=24), and 3-level (n = 6) cases making a total of 81 cages implanted and studied. The mean operative time was 132.7 minutes. In the group demonstrated significant improvements in NRS, AAOS-Modems disability outcome, and NDI scores after surgery (mean follow-up 12 months). The cervical lordosis at pre- and last follow-up period were 8.7 ± 2.2° and 8.3 ± 3.2°, respectively. Complication rate was 21.2%. Conclusions: TSC yielded satisfactory long-term clinical and radiological outcomes; this preliminary report can form the basis of a cost-benefit analysis study either prospectively or by way of meta-modelling comparing APC, LSC to TSC.